2018
DOI: 10.20964/2018.02.63
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Nanostructures of MoS2/Sisal Fiber Tubular Carbon as Anode Material for Lithium ion Batteries

Abstract: Environmentally friendly and low-cost MoS 2 /sisal fiber tubular carbon (MoS 2 /SFTC) nanohybrids have been prepared via a facile hydrothermal-anneal strategy, in which the tubular biomass carbon derived from natural sisal fibers as a conductive base. The as-prepared nanohybrids are characterized by Raman spectra, XRD, XPS, FESEM, TEM and EDS. It is shown that the sisal fiber tubular carbons with nanowrinkles and nanofolds were uniformly coated with vertical MoS 2 nanosheets on the surface. As an anode materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…As shown in Fig. 2B, four peaks appeared at about 533.4 eV, 532.4 eV, 531.6 eV, and 530.6 eV in O 1s, which are identified as combining energy peaks of O–CO, O–C, OC, and O–H, 40–42 respectively. In the case of C 1s, four peaks at the binding energies of about 289.1 eV, 286.1 eV, 285.0 eV, and 284.4 eV in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…As shown in Fig. 2B, four peaks appeared at about 533.4 eV, 532.4 eV, 531.6 eV, and 530.6 eV in O 1s, which are identified as combining energy peaks of O–CO, O–C, OC, and O–H, 40–42 respectively. In the case of C 1s, four peaks at the binding energies of about 289.1 eV, 286.1 eV, 285.0 eV, and 284.4 eV in Fig.…”
Section: Resultsmentioning
confidence: 91%
“…As illustrated in Figure S12, the (NH 4 ) 2 Mo 3 S 13 has a higher capacity than pure MoS 2. , In addition, the discharge capacity curves first decreased and then increased and eventually stabilized. The mechanism for storing Na + in the (NH 4 ) 2 Mo 3 S 13 anode will be studied in detail later.…”
Section: Results and Discussionmentioning
confidence: 99%
“…The tubular sisal fiber carbon was prepared based on the methods used in our previous work [22], and the preparation process is as follows:…”
Section: Preparation Of Tubular Sisal Fiber Carbonmentioning
confidence: 99%
“…Among many studies, it was found that the hard carbon derived from cellulose-rich sisal fibers, with the advantages of low cost, green, and sustainable bioresource, exhibits excellent electrochemical performance when used as an anode for LIBs. The main focus of our previous work was to modulate the structure of sisal fibers using chemical activation and calcination methods, and to obtain sisal fiber carbon with various morphologies and structures [22][23][24] (its chemical activation reagents were KOH and HCl). Generally, the ICE of hard carbon can be effectively improved by controlling the defect concentration and specific surface area [25], but developing appropriate structures to ensure structural stability and high Coulombic efficiency, without affecting the electrolyte-electrolyte interface behavior, remains a challenge.…”
Section: Introductionmentioning
confidence: 99%